Artificial inteligence approache to modeling of cutting force and tool wear relationships during dry machining - Kovač, Pavel; Savkovic, Boris; Rodić, Dragan; Mankova, Ildiko (Journal of Production Engineering, 2018)
In the paper numerical and experimental study for different cutting conditions according planning of experiment was carried out. Contribution was made during dry face milling process what contributes to sustainability of manufacturing processes. Cutting force components and parameters of tool wear versus time were pointed out. It was observed that cutting force components increase with time and/or tool wear. The relationships for cutting force components versus cutting depth, feed and tool wear parameters were expressed by regression analyse and artificial neural network.